Diet of selected species of babblers (Family : timaliidae) at Kampung Serasot and Kampung Bung Jagoi, Gunung Jagoi, Bau, Sarawak (Borneo) - Nur Shakirah, Binti Kamarul Zaman (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The diet of 23 individuals of family Timaliidae consisting of seven species of babblers namely, (Stachyris poliocephala), Chestnut-winged babbler (Stachyris erythroptera), Rufous-crowned babbler (Malacopteron magnum), Scaly-crowned babbler (Malacopteron cinnereum), Moustached babbler (Malacopteron magnirostre), Horsfield’s babbler (Malacocincla sepiaria), and Short-tailed babbler (Malacocincla malaccensis) was studied. Birds were captured at Kampung Serasot and Kampung Bung Jagoi, Bau District, Sarawak, Borneo on 8-12 November 2011 and 2-5 February 2012, respectively. About 0.2 ml of 1.5% potassium antimony tartrate were given to babblers so that they regurgitated the food items inside their crop. The regurgitated items, stomach contents and faecal samples of the same bird were all analyzed. The regurgitated item, digestive system and faeces of babblers were preserved using 70% alcohol in the field and examination of the stomach content was conducted at the Parasitology Laboratory at External Laboratory (EL), Universiti Malaysia Sarawak (UNIMAS). The insect parts used as main identification of insect order are body, head, mandibles, wings, elytra and legs. The study showed that the diet of babblers contains six insect orders that is, Coleoptera (40%), Hymenoptera (18.67%), Orthoptera (13.33%), Arachnida (9.33%), Diptera (8%), and unidentified order (10.67%).